Communicating, Networking: Interacting: The International Year of Global Understanding - IYGU - Robertson, Margaret E. (SpringerBriefs in Global Understanding, 2016)
Communication Studies; Sustainable Development; Communications Engineering, Networks; Computer Systems Organization and Communication Networks